HOW USEFUL AND IMPORTANT FOR HEALTHY OF PEOPLE TO PLAYING TENNIS. INTRODUCTION ABOUT TENNIS - Иминова З.Б. (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2023)
Annotation : This article contains information about tennis and its positive and effective sights, it’s two types with information about them. Tennis, original name lawn tennis, game in which two opposing players (singles) or pairs of players (doubles) use tautly strung rackets to hit a ball of specified size, weight, and bounce over a net on a rectangular court. Points are awarded to a player or team whenever the opponent fails to correctly return the ball within the prescribed dimensions of the court.